Validity of Research-Oriented General Physiology Learning Tools to Support Science Process Skills - Berlian, Liska; Taufik, Annisa Novianti; Mulyani, Siti Muhasitoh; Nulhakim, Lukman; Juansah, Dase Erwin (Jurnal Penelitian dan Pembelajaran IPA, 2023)
Students apply the science process skills to investigate scientific phenomena like scientists taught by science teachers who are committed and master the material, structure, and scientific methodology. The general physiology course equips animal and plant physiology knowledge in between science process skills as future junior high school science teachers. The course learning tool must attend to the demands. Research-based learning oriented to scientific processes can train science education students' science process skills. This study aimed to define the validity of research-oriented general physiology learning tools developed to support science process skills. Component learning tools are semester learning plans, textbooks, and assessment instruments. The validation of research-oriented general physiology learning tools developed to support science process skills rated 82.80% with a high category. The category shows that learning tools are worthy of empirical testing.